Perspectival Reversals of a Solid: A Phenomenal Description. (November 2014) - Deregowski, Jan B
The paper presents a phenomenal investigation of monocular perception of perspectival reversal of a conical shell. The inverted shell is seen as shorter than the stimulus, and both relative size of elements within it and movement within it appear to be affected by reversal. Similarity of the observed effects to those recorded in studies of afterimages are noted, as is similarity to reversals of Mach's Book.